Direct digital manufacturing of uniform thickness continuous fiber grid stiffened composites through tow spreading via roller based deposition - Ratkai, Harry, author; Radford, Donald, advisor; Yourdkhani, Mostafa, committee member; Heyliger, Paul, committee member (Colorado State University. Libraries, 2024)
Grid stiffened structures are an effective method for lightweighting designs. While continuous fiber composites are attractive materials for creating grid stiffened structures, there are two major impediments to the wider acceptance of such structures: the high capital costs for manufacturing and the material buildup at the crossover points. The high capital costs not only come from the complex tooling but also from the need to cure the parts after deposition. The material buildup at the crossover points is not only geometrically undesirable but can reduce the mechanical performance of the part. Many options to overcome this additional thickness have been implemented, but the majority cut the continuous fiber at the crossover, further reducing the performance. Previous work at Colorado State University has demonstrated that crossovers can be manufactured using a nozzle-based gantry printer and continuous glass fiber/PET commingled tow with a minimal thickness buildup at the crossover, all with radically reduced tooling, without compromising the structural performance. Unfortunately, the direct digital manufacturing system used did not utilize a cut and refeed system for the commingled tow; thus requiring the part to be made using continuous pathing or for a person to manually stop, cut and restart the tow at the end/beginning of each discrete path. These shortfalls of the nozzle-based printer make this technology, in its current form, impractical for adoption by industry. This work details the development of a robotic end effector for a new manufacturing method utilizing a heated roller for deposition and a programmable cut and refeed system. Initially, a comparison of the two methods of deposition, nozzle and roller, was done; both systems made crossover samples where part thickness and void and fiber volume fractions were measured. Next, an optimization of process parameters was performed on the beam and crossover sections, separately, for the roller-based end effector. Both the beams and crossovers were evaluated using thickness measurements, void and fiber volume fraction measurements and microscope imaging. Finally, a molding shoe was attached to the end effector to determine the effectiveness of molding the beam side walls, in-situ. It was demonstrated that the roller-based system can manufacture grid stiffened parts with less thickness deviations and fewer voids then the nozzle-based system. Additionally, optimized processing parameters were found for beams at three different deposition speeds, 450mm/min, 600mm/min and 750mm/min. Under the best conditions. The system is capable of direct digital manufacture of continuous fiber reinforced composite grids with under 2% void content. By slowing the deposition speed and increasing the consolidation force at the crossover points, the system is able to spread and thin the tow, thus, minimizing the thickness buildup at the crossover points. Using the understanding developed in determining optimized parameter two additional demonstrations of the capabilities of the system were completed: a preliminary example of full molding of the grid cross-section and the manufacture of curvilinear grids via in-plane steering. Combined, the outcomes demonstrate that a roller-based system with cut and refeed can produce grid stiffened structures with discrete fiber paths, that have crossovers of uniform thickness, at higher deposition rates than previous nozzle-based technology.
Keywords: continuous fiber; thermoplastic composites; grid stiffened; composite materials